Philosophy of God in the Perspective of Western Views, Islamic Views, and Revealed Religions (Analysis of the History of Human Thoughts About God) - Didik Himmawan; Salma Fitri; Siti Komalasari (Konsultan Jurnal Ilmiah Indonesia, 2025)
The purpose of writing this article is to find out the Philosophy of God in the Perspective of Western Views, Islamic Views, and Revealed Religions (Analysis of the History of Human Thoughts About God). This research method uses a qualitative research method (Qualitative Research) with a qualitative library study approach (Library Research). Reference sources or libraries are from articles, journals, and reference books that discuss the Philosophy of God in the Perspective of Western Views, Islam, and Revealed Religions. The results of this study are that the philosophy of God is a study of God that uses reason. Philosophy remains a useful tool for contemplating and deepening beliefs. The Philosophy of God in the Western tradition is a dynamic and ever-evolving field. While the Philosophy of God in Islam provides a comprehensive framework for thinking about God. By combining reason and revelation, Islam offers a deep understanding of the Creator and the relationship between humans and Him. Human thought about God has undergone a very long and complex development. The history of human thought about God shows that humans always try to find meaning and purpose in life. The concept of God continues to evolve along with the development of human knowledge and understanding of the universe.